B.F. Skinner and World Behavior Analysis Day - E.V. Khilkevich (Moscow State University of Psychology and Education, 2021)
The World Behavior Analysis Day was held in 2021 for the first time, raising the public awareness about this actively developing scientific discipline. This date, March 20 was chosen to commemorate the birthday of Burrhus Frederick Skinner, an outstanding psychologist of the XX century, the founder of behavioral analysis and radical behaviorism.